Design of intelligent meal delivery robot system based on binocular vision - Pei Hanhua; Qin Huibin (Dianzi Jishu Yingyong, 2021)
With the increasing aging of Chinese society, the shortage of labor force will seriously hinder the development of social economy. Intelligent robots slowly integrate into human production and life, and gradually begin to play an increasingly important role in replacing humans. This article designs and implements an intelligent meal delivery robot system based on binocular vision to solve the problem of large path deviation in the meal delivery tracking process of traditional meal delivery robots. The hardware circuit of the whole system is composed of image acquisition module, power supply module, motor drive module and so on. The software uses the stereo matching algorithm to design the optimal path. Through experimental verification, this program is practical and reliable, and it has realized the intelligentization of restaurant meal delivery, and has good application and promotion value.